KEPEMILIKAN RUMAH DINAS OLEH PURNAWIRAWAN TNI BERDASARKAN PERUNDANG-UNDANGAN - Intan Ghina Maurizka; Maurizka Ananda Rahmadhani (Law Review, 2019)
Land is a symbol of prosperity for an agrarian country. Having land rights that have been regulated by law, for example is absentee land which is ownership of a number of land outside of the place where he is domiciled. Civil servants or military officials are given specificity to occupy official houses provided by the state to ensure the effectiveness of time in carrying out their work. Specificity for military officials (TNI) to own land because military officials often have difficulty in determining the domicile caused by their official duties. And there are exceptions to land ownership for retired military officials.